2018
DOI: 10.1542/hpeds.2017-0158
|View full text |Cite
|
Sign up to set email alerts
|

Teamwork on Rounds on an Inpatient Ward Team: An Ethnographic Study

Abstract: Our findings aligned with some, but not all, teamwork principles from TeamSTEPPS; misalignment may be due to contextual factors, such as the need to provide medical education and the development of grassroots routines (eg, running the list). Context is a key consideration when developing interventions to enhance teamwork on inpatient medical wards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Despite the potential value of ward rounds in teaching trainees to generate diagnostic hypotheses and differential diagnoses, to select investigations and treatments and to make decisions regarding patient care, 10 it has been suggested that more time is devoted to developing care plans than to discussing diagnoses during team discussions 11 . Prior studies on ward rounds in teaching hospitals have examined the extent to which rounds are dedicated to presenting patients and discussing patient care 12–19 . However, how clinical (diagnostic) reasoning occurs in team discussions is not well understood, such as the communication processes among team members and factors that influence them (e.g., team composition and hierarchy, environmental factors and location of discussions and contextual factors such as time and external pressures).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the potential value of ward rounds in teaching trainees to generate diagnostic hypotheses and differential diagnoses, to select investigations and treatments and to make decisions regarding patient care, 10 it has been suggested that more time is devoted to developing care plans than to discussing diagnoses during team discussions 11 . Prior studies on ward rounds in teaching hospitals have examined the extent to which rounds are dedicated to presenting patients and discussing patient care 12–19 . However, how clinical (diagnostic) reasoning occurs in team discussions is not well understood, such as the communication processes among team members and factors that influence them (e.g., team composition and hierarchy, environmental factors and location of discussions and contextual factors such as time and external pressures).…”
Section: Introductionmentioning
confidence: 99%
“…11 Prior studies on ward rounds in teaching hospitals have examined the extent to which rounds are dedicated to presenting patients and discussing patient care. [12][13][14][15][16][17][18][19] However, how clinical (diagnostic) reasoning occurs in team discussions is not well understood, such as the communication processes among team members and factors that influence them (e.g., team composition and hierarchy, environmental factors and location of discussions and contextual factors such as time and external pressures). Given the potential value of ward rounds for learning about team clinical reasoning, it is important to understand how teams communicate clinical reasoning in this complex learning environment to develop strategies that may enhance the teaching and learning of clinical reasoning.…”
Section: Introductionmentioning
confidence: 99%